2006
DOI: 10.1038/sj.onc.1209449
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase WNK3 increases cell survival in a caspase-3-dependent pathway

Abstract: The subfamily of WNK (with no K ¼ lysine) protein kinases has four human members and germline mutations in the WNK1 and WNK4 genes were recently found to cause pseudohypoaldosteronism type II, a familial hypertension disease. Here, we describe cloning and functional analysis of a further WNK member, human WNK3. Endogenous WNK3 protein is an active protein kinase when immunoprecipitated from cells and its overexpression increases the survival of HeLa cells by delaying the onset of apoptosis. Suppression of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
1
38
1
Order By: Relevance
“…WNKs have been proposed to have many functions besides the modulation of electroneutral cation-coupled chloride cotransporters, including regulating basic cellular processes such as mitosis (25), apoptosis (27) and neoplastic transformation (19), regulating synaptagmin 2 (15), and interacting with many other kinases, like TGF-␤ (14), MAP kinases (31), and the STE20-related alanine/proline-rich kinases SPAK and OSR1 (28) (for an excellent review, see Ref. 16).…”
Section: Effects Of the Catalytically Inactive Wnk3 Variants On The Cmentioning
confidence: 99%
“…WNKs have been proposed to have many functions besides the modulation of electroneutral cation-coupled chloride cotransporters, including regulating basic cellular processes such as mitosis (25), apoptosis (27) and neoplastic transformation (19), regulating synaptagmin 2 (15), and interacting with many other kinases, like TGF-␤ (14), MAP kinases (31), and the STE20-related alanine/proline-rich kinases SPAK and OSR1 (28) (for an excellent review, see Ref. 16).…”
Section: Effects Of the Catalytically Inactive Wnk3 Variants On The Cmentioning
confidence: 99%
“…ERK5 is implicated in proliferative as well as developmental pathways, notably in cardiovascular development (Nicol et al, 2001;Yan et al, 2003). WNK3 pro-motes cell survival by inhibiting caspase-3 (Verissimo et al, 2006). In addition, WNKs modulate TGFβ-Smad signaling (Lee et al, 2007).…”
Section: Role Of Wnk Kinases In Cell Signaling Proliferation Survivmentioning
confidence: 99%
“…However, neither knockdown nor overexpression of WNK1 had any effect on neuronal survival, indicating that WNK1 is not involved in the regulation of neuronal apoptosis (5). Among the four known WNK family members, only WNK3 has been reported to regulate cell survival (17). In this study, we found that WNK3 had a potent prosurvival effect on serum-deprived cortical neurons.…”
Section: Discussionmentioning
confidence: 54%
“…To further assess the role of WNK3 kinase activity in neuronal apoptosis, we expressed a transgenic form of WNK3 containing the entire catalytic domain, WNK(49 -436) (27), or a kinase-dead mutant form of the same transgene, WNK3(49 -436)K159M (17). Both constructs were cloned into pEGFP-N1 and transfected into cultured cortical neurons.…”
Section: Effect Of Lingo-1 On Neuronalmentioning
confidence: 99%
See 1 more Smart Citation